2022
DOI: 10.3390/jcm11030732
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia in Adolescents with Acne: Association with Quality of Life Impairment and Stigmatization

Abstract: Alexithymia seems to be more common among patients with skin diseases. However, studies on acne patients are very limited. We conducted this study to evaluate alexithymia in adolescents with acne. In our cross-sectional study, 730 high school students (mean age: 17.05 ± 1.18 years) were recruited. The Toronto Alexithymia Scale (TAS-20) was used to measure alexithymia, the Dermatology Life Quality Index (DLQI) was employed to study quality of life (QoL), and the 6-item Stigmatization Scale (6ISS) was used to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Several studies demonstrated an increased prevalence of alexithymia in common dermatological disorders, including psoriasis, acne, hidradenitis suppurativa, pruritus and others [6,[13][14][15]39]. Some of them, as acne for example, affect mainly adolescents [40]. Therefore, taking into consideration that alexithymia may have a negative impact on the final result of the therapeutic process of many conditions [18], the knowledge of prevalence and gender differences of alexithymia in selected populations might be of value.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated an increased prevalence of alexithymia in common dermatological disorders, including psoriasis, acne, hidradenitis suppurativa, pruritus and others [6,[13][14][15]39]. Some of them, as acne for example, affect mainly adolescents [40]. Therefore, taking into consideration that alexithymia may have a negative impact on the final result of the therapeutic process of many conditions [18], the knowledge of prevalence and gender differences of alexithymia in selected populations might be of value.…”
Section: Discussionmentioning
confidence: 99%
“…Acne is regarded as one of the most common reasons for visiting the [ 25 ] doctor. The disease has a profound negative influence on patients’ well-being [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Therefore, the European Dermatology Forum S3-Guideline for the Treatment of Acne strongly recommends consideration of health-related QoL in acne patients as routine daily measurement as well as the assessment of treatment effectiveness [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common location of acne is the face; however, the lesions frequently appear on the chest and upper back [ 1 ]. Although acne is not a life-treating condition, independently of its clinical severity, it heavily influences patients’ psychosocial status [ 5 , 6 , 7 , 8 , 9 ]. Acne patients have been demonstrated to have significantly lower quality of life (QoL) [ 9 , 10 ] and a higher level of stigmatization [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acne is a chronic inflammatory disease of the pilosebaceous unit, involving increased androgen-induced sebum production, abnormal keratinization of the pilosebaceous duct and an immune response to colonization by Cutibacterium acnes (formerly Propionibacterium acnes ) (1, 2). Acne is estimated to affect 9.4% of the world’s population, making it the eighth most prevalent disease worldwide, affecting 90% of adolescents and young adults (3, 4).…”
Section: Introductionmentioning
confidence: 99%
“…The visibility, chronicity and recurrent course of many skin lesions contribute to various psychosocial disorders, consequences of skin diseases. Patients with dermatoses are at increased risk of developing depression, anxiety, and suicidal ideation (4, 8, 9). In our society today, if certain social parameters are not met in physical appearance, adolescents suffer from bullying by their peers, acne can lead to emotional stress and the impact on quality of life can be significant (10).…”
Section: Introductionmentioning
confidence: 99%